A novel secure routing scheme using probabilistic modelling for better resistivity against lethal attacks - Jyoti Neeli; N. K. Cauvery (Institute of Advanced Engineering and Science, 2020)
Study towards Wireless Adhoc Network dates two decades back with various researchers evolving up with new solutions towards addressing its problems. Irrespective of various other problems, the issues related to the secure routing is yet unsolved owing to massively increasing fatal strategies of the adversary. Review of existing literature shows that the existing secure routing scheme can only govern over the stated attacks reducing the applicability in case of dynamic attacks. Therefore, this manuscript introduces a novel probabilistic model which offers the capability to wireless nodes to identify the malicious behavior and react accordingly. Different from existing intrusion prevention system, the proposed system allows the malicious node to participate in the data forwarding process and exhaust its resources with no chance of launching an attack. The simulated outcome of the study shows that the proposed secure routing scheme offers better data forwarding characteristic in contrast to the existing system in the aspect of intrusion detection and secure data transmission.